Antidepressant-like effect of Hoodia gordonii in a forced swimming test in mice: evidence for involvement of the monoaminergic system - Citó,M.C.O. (2015)
Hoodia gordonii is a plant species used traditionally in southern Africa to suppress appetite. Recently, it has been associated with a significant increase in blood pressure and pulse rate in women, suggesting sympathomimetic activity. The present study investigated the possible antidepressant-like effects of acute and repeated (15 days) administration of H. gordonii extract (25 and 50 mg/kg, po) to mice exposed to a forced swimming test (FST). Neurochemical analysis of brain monoamines was also carried out to determine the involvement of the monoaminergic system on these effects. Acute administration of H. gordonii decreased the immobility of mice in the FST without accompanying changes in general activity in the open-field test during acute treatment, suggesting an antidepressant-like effect. The anti-immobility effect of H. gordonii was prevented by pretreatment of mice with PCPA [an inhibitor of serotonin (5-HT) synthesis], NAN-190 (a 5-HT1A antagonist), ritanserin (a 5-HT2A/2C antagonist), ondansetron (a 5-HT3A antagonist), prazosin (an α1-adrenoceptor antagonist), SCH23390 (a D1 receptor antagonist), yohimbine (an α2-adrenoceptor antagonist), and sulpiride (a D2 receptor antagonist). A significant increase in 5-HT levels in the striatum was detected after acute administration, while 5-HT, norepinephrine and dopamine were significantly elevated after chronic treatment. Results indicated that H. gordonii possesses antidepressant-like activity in the FST by altering the dopaminergic, serotonergic, and noradrenergic systems.